Vaginal vault smear cytology in detection of recurrence after hysterectomy for early cervical cancer. Issue 7 (14th March 2022) - Grace, Leah; Sanday, Karen; Garrett, Andrea; Land, Russell; Nicklin, Jim; Obermair, Andreas; Rao, Archana; Tang, Amy; Allanson, Emma R
Abstract : Objective: To determine the role of vaginal vault cytology as a surveillance tool for the detection of recurrence in patients with early stage cervical cancer treated with hysterectomy without adjuvant therapy. Methods: A retrospective cohort study was conducted of all women with cervical cancer treated with a hysterectomy from January 2000 to July 2016 at the Royal Brisbane & Women's Hospital, Australia. Women included were diagnosed with the equivalent of International Federation of Gynecology and Obstetrics (FIGO) 2018 stage 1A1 to 1B3 squamous cell carcinoma, adenocarcinoma, or adenosquamous carcinoma, received either simple or radical hysterectomy with or without pelvic lymph node dissection, and did not receive adjuvant therapy. Age, stage, histology, surgical procedure, and details of individual surveillance regimens including examination findings and indications and results for all vault cytology tests performed in the first 5 years following surgical management were collected. Results: A total of 155 women met the inclusion criteria. Most cases were FIGO 2018 stage 1B1 (61.9%) and squamous cell carcinoma (64.5%). Included women underwent a median of 80 months of surveillance (range 25–200, IQR 64–108). In the first 5 years of surveillance, there were a total of 1001 vault cytology smears performed, with a median of 6 smears (IQR 5–9) per woman. A total of 19 smears were abnormal (1.9%). Of the cohort of 155 women, 19 (12.3%) had an abnormality detected; 1 (0.65%) had a high-grade intraepithelial abnormality and 2 (1.3%) had recurrences detected on cytology; however, a lesion was also seen and biopsied in all three women. A total of 16 of 1001 smears (1.6%) had low-grade abnormalities detected, all of which resolved with clinical observation only. All were alive and well at last review. There were in total 6 (3.9%) recurrences, 2 (33%) of which had abnormal cytology as above, and all of which had a lesion to biopsy and/or abnormal medical imaging. Conclusions: The routine use of vaginal vault cytology in surveillance following hysterectomy for early stage cervical cancer did not appear to alter the detection of recurrent malignancy.